Com palavras não sei dizer: ressignificando o cuidado através da música em pós-operatório cardiopediátrico - Odemir Pires Cardoso; Mara Marusia Martins Sampaio Campos; Mônica Cordeiro Ximenes de Oliveira; Maria Tereza Aguiar Pessoa Morano; Maria Valdeleda Uchoa Morais Araújo; Kellen Yamille dos Santos Chaves (Universidade Federal do Ceará, 2017)
Objective: to understand the new meanings that music promotes in the care of children in cardio pediatric surgery postoperative. Methods: qualitative research with professionals of the multi professional health team through a semi-structured interview based on the Content Analysis method. Results: professionals perceived the Pediatric Intensive Care Unit as a scenario susceptible to deterioration in the quality of care. In addition, they considered that the use of music, as an integrative and complementary therapy, fostered the production of senses in health care, proving it capable of providing relaxation, distraction, well-being, pleasant memories and comfort to professionals and hospitalized children. Conclusion: music contributed to give new meaning to care optimizing humanization and restructuring health promotion processes. The experience provided reflections, skills, emotional expression, sensations and feelings such as relaxation, distraction and well-being in the multi professional team. Child care has been expanded, combining the technological arsenal with concern for comfort and emotional state.